Dietary habits and nutritional status of adolescents - Srđan Živanović; Veselinka Kulić; Natalija Hadživuković; Jelena Pavlović; Sandra Matović (Биомедицинска истраживања, 2020)
The concept of proper nutrition implies meeting the needs of the body concerning daily energy intake and a sufficient amount of nutrients and protective substances necessary to maintain the physiological functions of the body and its health. Nutrients are divided into macronutrients (proteins, carbohydrates and fats) and micronutrients (vitamins and minerals). Accelerated growth and development during adolescence increase nutrient requirements. Therefore, energy and nutrition requirements must meet the needs of adolescents. During their growth and development, there is an increased need for vitamins and minerals, especially for calcium, iron, zinc and vitamin D. During intensive growth, adolescents require more vitamins, especially B-complex vitamins and vitamin C, the intake of calcium and phosphorus is necessary as well, and the insufficient needs for proteins affect the development of muscles and energy levels. Proper nutrition and eating habits during the period of growth are of the utmost importance for the appropriate physical, psychosocial and cognitive growth and development of a child. Eating disorders usually occur as a result of low or high energy intake, and the most common types of these disorders are anemia, anorexia and bulimia, obesity and comorbidities, and poor eating habits. When it comes to the implementation of various programs concerning the prevention of bad eating habits and eating disorders, the school management, expert teams and student parents should bear the overall responsibility. Once or twice a year, preventive check-ups and BMI measurements are recommended to identify eating disorders.
Keywords: diet; children; nutritional status; eating habits